2015
DOI: 10.1080/02827581.2015.1078405
|View full text |Cite
|
Sign up to set email alerts
|

Copper and zinc dynamics in foliar litter during decomposition from gap center to closed canopy in an alpine forest

Abstract: Forest gap in alpine forests may redistribute the hydrothermal conditions in winter and growing season, which may affect the releases of copper and zinc in foliar litter during decomposition. However, the details of this process are largely unknown. Foliar litters of willow (Salix paraplesia), larch (Larix mastersiana), fir (Abies faxoniana), azalea (Rhododendron lapponicum), birch (Betula albosinensis) and cypress (Sabina saltuaria) were selected in an alpine forest of eastern Tibetan Plateau. The litterbags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The observed Cu and Zn immobilization may respond to accumulation from the environment (soil and atmospheric deposition) as found by several authors for elements such as Fe, Cu, Mn, or Zn (He et al 2016;Laskowski et al 1995;Pourhassan et al 2016).…”
Section: Nutrient Release In Decomposing Needle Litter Throughout Timesupporting
confidence: 64%
See 1 more Smart Citation
“…The observed Cu and Zn immobilization may respond to accumulation from the environment (soil and atmospheric deposition) as found by several authors for elements such as Fe, Cu, Mn, or Zn (He et al 2016;Laskowski et al 1995;Pourhassan et al 2016).…”
Section: Nutrient Release In Decomposing Needle Litter Throughout Timesupporting
confidence: 64%
“…They found a decrease in litter moisture after thinning and lower decomposition rates together with an increase in N and P immobilization and a decrease in Ca immobilization. He et al (2016) also observed higher immobilization of Cu and Zn in areas located under closed canopies (higher local basal area) compared to areas in forest gaps (lower local basal area) for several species in an Alpine forest in China. The differing trends found in these studies may be related to different microclimatic effects of the decrease in local basal area, with higher solar radiation reaching the soil and lower topsoil humidity instead of lower rainfall interception and higher topsoil humidity.…”
Section: Effect Of Local Basal Area On Nutrient Release From Littermentioning
confidence: 74%
“…A previous study found that the contents of Zn and Mn decreased by 24 and 43 % from the initial values, respectively, after 7 years in decomposing spruce needle litter on the forest floor (Lomander and Johansson 2001). However, recent studies have suggested that a net accumulation of Mn, Zn, and Cu could occur in decomposing litter after 1 year of incubation on forest floors (Jonczak et al 2014;He et al 2015), and these elements plus Fe and Al were also found to accumulate during river litter decomposition in this study. Numerous studies have demonstrated that the concentrations of most metallic elements in litter increase considerably as decomposition progresses (Windham et al 2004;Du Laing et al 2006), and some studies have also suggested that metallic elements will be released when the content exceeds a certain threshold (Lomander and Johansson 2001;Edmonds and Tuttle 2010;Aponte et al 2012).…”
Section: Discussionmentioning
confidence: 67%
“…Major elements, such as K, Ca, and Mg, were reported to release during litter decomposition on forest floors (Staaf and Berg 1982;Edmonds and Tuttle 2010), whereas trace elements, such as sodium (Na), manganese (Mn), Zn, and Cu, preferentially retain and show increasing concentrations during the early stages of litter decomposition on forest floors (Edmonds and Tuttle 2010;Jonczak et al 2014;He et al 2015). Plant litter species and plant functional traits are the predominant factors controlling litter decomposition at both local and global scales (Cornwell et al 2008;Makkonen et al 2012); litter quality should thus significantly influence the dynamics of elements in decomposing litter.…”
Section: Introductionmentioning
confidence: 99%
“…The observed Cu and Zn immobilization may respond to accumulation from the environment (soil and atmospheric deposition) as found by several authors for elements such as Fe, Cu, Mn, or Zn (Laskowski et al 1995, He et al 2016, Pourhassan et al 2016).…”
Section: Nutrient Release In Decomposing Needle Litter Throughout Timesupporting
confidence: 63%